FAT COMPOSITION AND FATTY ACID CHARACTERIZATION OF CHIA SEED (Salvia hispánica L.) - Mosquera Quelal, María (2017)
The alterations of the lipid metabolism and the uncertainty at the moment of selecting beneficial foods to the human body lead to the investigation of omega fatty acids. The study is based on the evaluation of the effect of three preparation methods of chía seed, before getting the oil through two extraction methods and the characterization of the lipid fraction of chia seed (Salvia hispánica L.) from Colta-Ecuador. The oil yield of the conditioned seeds showed statistical differences. Regarding the extraction method, the differences were highly significant, the use of ether in the Soxhlet equipment showed the superiority in the oil performance in a relation of approximately 2:1 versus immersion in hexane. The presence and the content of fatty acids was determined by the use of a gas chromatograph with FiD detector Agilent Technologies 5975C brand, fatty acids were separated with a capillary column fused of silica SUPELCO 2560 with film thickness of 100 m x 0,25 mm i.d. x 0,20 m as a stationary phase; the oven temperature was programmed from 140 °C (5 minutes), to 240 °C (15 minutes), the injector was used at 260 °C with injection volume of 2µl, Split:40:1 and the Helium carrier gas 20cm/s at 175 °C as a mobile phase. Fatty acids predominantly presented in the oil were linolenic and linoleic, polyunsaturated fatty acids of the omega family. The results obtained revealed that chia oil is a healthy ingredient or additive for the elaboration of the functional foods rich in omega-3 fatty acids.